2021
DOI: 10.5194/bg-2021-133
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Representativeness assessment of the pan-Arctic eddy-covariance site network, and optimized future enhancements

Abstract: Abstract. Large changes in the Arctic carbon balance are expected as warming linked to climate change threatens to destabilize ancient permafrost carbon stocks. The eddy covariance (EC) method is an established technique to quantify net losses and gains of carbon between the biosphere and atmosphere at high spatio-temporal resolution. Over the past decades, a growing network of terrestrial EC tower sites has been established across the Arctic, but a comprehensive assessment of the network’s representativeness … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 61 publications
0
17
0
Order By: Relevance
“…Furthermore, year-round turbulent flux measurements (i.e. sensible and latent heat flux) are especially scarce for all vegetation types 53 . Finally, SEB observations for barren tundra are largely missing, while this type shows largest differences in surface energy fluxes to other tundra vegetation types in the limited data available for this study.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, year-round turbulent flux measurements (i.e. sensible and latent heat flux) are especially scarce for all vegetation types 53 . Finally, SEB observations for barren tundra are largely missing, while this type shows largest differences in surface energy fluxes to other tundra vegetation types in the limited data available for this study.…”
Section: Discussionmentioning
confidence: 99%
“…Given the size of the Arctic region, the rugged environmental conditions, and limited accessibility, it has been a challenge to detect carbon cycle change over the region as a whole. There are notable well-studied sites with a history of scientific research that have provided a wealth of mechanistic insight, but the limited number has been a barrier toward understanding and quantifying the aggregate response of the entire region (60)(61)(62)(63)(64)(65)(66). At the same time, the history of the region provides inference into past interactions between terrestrial ecosystems and the atmosphere for CO 2 , which is the largest carbon flux.…”
Section: Carbon Dioxide Emissions: Observationsmentioning
confidence: 99%
“…This approach provides a unit-less relative measure of representativeness between a location defined as the medoid of each cluster and every other location within that cluster. Although studies of this nature often define representativeness relative to a research site (Pallandt et al, 2021), this study identified positions within the landscape that are more representative of the medoid condition of the cluster and measured the distance from this medoid to understand how representative any location within a cluster is to the medoid condition. To extrapolate the cluster and distance layers across the entire US beyond the 20,000-pixel subsample, we fit a Random Forest model with the package randomForest (Liaw and Wiener, 2002) to model the first and second MDS dimension using the ecotype and climate layers as predictors.…”
Section: Climate and Dominant Land Cover Typesmentioning
confidence: 99%